ANALISIS PENGARUH RASIO KEUANGAN DAN PERTUMBUHAN ASET TERHADAP DEVIDEN PER SHARE PADA INDUSTRI WHOLE SALE AND RETAIL TRADE DI BURSA EFEK INDONESIA - Mulia Inda Purwati (Fakultas Hukum dan Ekonomi Bisnis, 2020)
This study is performed to examine the effect of Current ratio, Cash ratio, Debt toTotal Equity (DER), Return on Investment (ROI), Earning per Share (EPS), Asset Growthtoward Dividend per Share (DPS) in industry Wholesale and Retail Trade that is listed in BEI.The objective of this study is to scale and analyze the effect of the company financial ratiosperformance (Current ratio, Cash ratio, Debt to Total Equity (DER), Return on Investment(ROI), Earning per Share (EPS), Asset Growth toward Dividend per Share (DPS) in industryWholesale and Retail Trade that is listed in BEI) over period 2009 - 2012. Sampling techniqueused here is purposive sampling on criterion (1) the company that trade their stocks in BursaEfek Indonesia (BEI); (2) the company that represents their financial report per December 2009-2012; and (3) the company that continually share their dividend per December 2009-2012. Thedata is obtained based on Indonesian Capital Market Directory (ICMD 2012 and 2013)publication. It is gained sample amount of 15 companies from 30 companies those are listed inBEI. While simultaneously (Current ratio, Cash ratio, Debt to Total Equity (DER), Return onInvestment (ROI), Earning per Share (EPS), Asset Growth) proof significantly influent DPS inWholesale and Retail Trade industry in the level less than 5%. Predictable of the seven variablestoward DPS is 68,90% as indicated by adjusted R square that is 68,90% while the rest 31,10% isaffected by other factors is not included into the study model.